Das Hohe Thor Fr. L. Meyer. - Meyer, Friedrich Leonhard (1842-po 1880) (s.n., 1879)
Przedstawia Bramę Wyżynną w Gdańsku wraz z wieżą Katowni, widziane od północnego-zachodu, w stanie po przebudowie w 1879 r.